QoS-aware middleware for ubiquitous and heterogeneous environments. - Nahrstedt, K. (IEEE Communications magazine)
Middleware systems have emerged to support applications in heterogeneous and ubiquitous computing environments. Specifically, future middleware platforms are expected to provide quality of service support, which is required by a new generation of QoS-sensitive applications such as media streaming and e-commerce. This article presents four key aspects of a QoS-aware middleware system: QoS specification to allow description of application behavior and QoS parameters; QoS translation and compilation to translate specified application behavior into candidate application configurations for different resource conditions; QoS setup to appropriately select and instantiate a particular configuration; and finally, QoS adaptation to adapt to runtime resource fluctuations. We also provide a comparison of existing QoS-aware middleware systems in these four aspects